A Delayed Diagnosis of Hemorrhagic Shock in a Patient with Alcoholic Cirrhosis and Ascites on Bedside Ultrasound - Madeline Bach; Julian Choi; Rory A. Smith; Sarkis Arabian (Case Reports in Critical Care)
Undifferentiated shock is a common and challenging problem in critical care. We present a case of hemorrhagic shock due to splenic and hepatic lacerations diagnosed by bedside paracentesis, initially misclassified as septic shock due to suspected spontaneous bacterial peritonitis (SBP). Case. A 47-year old man with a history of reported alcoholic cirrhosis and ongoing heavy alcohol use was brought to the emergency room after a syncopal event. He was found to be anemic (hemoglobin 9.9 g/dl) and hypotensive with a blood pressure of 64/34. Despite crystalloid infusion he remained hypotensive and required vasopressor support with norepinephrine. Bedside ultrasound revealed moderate ascites and as there was no evidence of active bleeding, his shock was attributed to sepsis due to SBP. A bedside paracentesis was performed which revealed gross blood. A repeat hemoglobin returned at 4.4 g/dl. Massive transfusion protocol was initiated and interventional radiology was emergently consulted due to concerns for intraabdominal hemorrhage; general surgery deemed the patient too unstable for surgical intervention. Angiogram revealed a splenic laceration and possible hepatic laceration, both embolized successfully. Internal medicine practitioners should keep the differential of hemorrhagic shock due to intraabdominal organ injury in mind for patients with undifferentiated shock.